Endemic bats (Mammalia: Chiroptera) of Colombia: State of knowledge, distribution, and conservation - Héctor E. Ramírez-Chaves, Elkin A. Noguera-Urbano, Darwin M. Morales-Martínez, Danny Zurc, Andrés Felipe Vargas-Arboleda, Hugo Mantilla-Meluk (Universitas Scientiarum)
Colombia, with 209 species, is one of the richest countries in terms of bat diversity. This high bat diversity is comprised in nine families and 72 genera. A total of eight species of the families Emballonuridae (n = 1) and Phyllostomidae (n = 7) are listed as endemic to the country. In spite the relevance of Colombia in bat diversity, little is known of these endemic species which are mostly known from the type locality (n = 4), whereas for others (n = 2), their taxonomic status is uncertain. Here, available information of endemic bats from Colombia is compiled, and new information on their distribution and conservation is provided. The most included species in publications including the original description (n = 15) was Lonchorhina marinkellei. The only distribution pattern observed for the species evaluated was for Carollia monohernandezi and Vampyressa sinchi that might overlap distributions in the eastern slopes of the Eastern Cordillera. Most endemic species are from the Andean and inter-Andean regions of the country (n = 6). At national level, there are no endemic species in any threatened category; however, at least one species (Lonchorhina marinkellei) is considered as Vulnerable (VU) and one (Saccopteryx antioquensis) as Endangered (EN) by the International Union for Conservation of Nature - IUCN